2017
DOI: 10.1093/cvr/cvx003
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic manipulation of anatomical re-entry by light-guided generation of a reversible local conduction block

Abstract: Anatomical re-entry in ventricular tissue can be manipulated by optogenetic induction of a local and reversible conduction block in the re-entrant pathway, allowing effective re-entry termination. These results provide distinctively new mechanistic insight into re-entry termination and a novel perspective for cardiac arrhythmia management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…One possible explanation could be the change in penetration depth when using higher light intensities for photostimulation, hence depolarizing a greater number of cells and creating a thicker reversible conduction pattern. This was also described by Watanabe et al in experiments with ventricular slices, where they showed a temporal decrease on the effective size available for the arrhythmia to wander (Watanabe et al, 2017 ). In their work, Watanabe et al proved that by increasing the transmurality of illumination, the chances of terminating an anatomical re-entry on the slices increased.…”
Section: Discussionsupporting
confidence: 68%
“…One possible explanation could be the change in penetration depth when using higher light intensities for photostimulation, hence depolarizing a greater number of cells and creating a thicker reversible conduction pattern. This was also described by Watanabe et al in experiments with ventricular slices, where they showed a temporal decrease on the effective size available for the arrhythmia to wander (Watanabe et al, 2017 ). In their work, Watanabe et al proved that by increasing the transmurality of illumination, the chances of terminating an anatomical re-entry on the slices increased.…”
Section: Discussionsupporting
confidence: 68%
“…On the contrary, at r C >1.10 mm, detachment and relocation was possible only when there was physical overlap between the inhomogeneities, or the two inhomogeneities were so close that the cells occupying the domain space between them constituted part of the composite inhomogeneity (conduction+light-induced), due to the inexcitability zone created by depolarization gradients of the light-induced inhomogeneity [38]. At r C >1.10 mm and > + d r r C L ( ), relocation occurred very rarely (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Since successful application of optogenetics depends on production of a photocurrent large enough to trigger depolarization, expression levels can be critical determinants of experimental outcome. A number of viral [18,25,29,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] and non-viral methods [9,10,25,29,31,32,48,[54][55][56][57][58][59][60][61][62][63] have been successfully applied to the cardiomyocyte. For in vivo cardiac application tissue tropism with adeno-associated virus (AAV) types 1 or 6 might be preferable to type 9 used in vitro [64].…”
Section: Optogenetic Tools and Their Deliverymentioning
confidence: 99%
“…1 ) are possible, and can be combined with surface electrodes [ 10 , 50 , 60 , 61 ] pacing electrodes ( e.g . to trigger ventricular tachycardia [ 31 ]) or imaging based mapping of tissue level activation [ 32 , 51 , 53 , 60 , 61 ]. Applications have tended to focus on dissecting out the role of the autonomic nervous system, as expression of the optical control tool can be restricted to certain cell types, or investigation the potential for optical pacing or defibrillation as an alternative to the current electrode based methods.…”
Section: Expanded Examplesmentioning
confidence: 99%